Impact of Foreign Direct Investment on Nigeria’s Agricultural Sector (1981 to 2019) - Ogbanje, Elaigwu Christopher; Salami, Abubakar Onoja (International Journal of Environment, Agriculture and Biotechnology, 2022)
The need to augment the financial policy interventions of the Central Bank of Nigeria in the agricultural sector is sine qua non. Since agriculture is still the mainstay of Nigeria’s economy, its reliance on foreign direct investment (FDI) ought to be ascertained. Consequently, this study investigated the impact of foreign direct investment on Nigeria’s agricultural sector. Time series data between 1981 and 2019 were obtained from the databases of the Central Bank and Food and Agriculture Organisation. The Augmented Dickey-Fuller test shows that the variables were I(1). Johansen’s co-integration test suggested long-run relationship among the variables. Findings revealed slower acceleration of agricultural productivity (6.28) than FDI (17.99). Also, FDI and exchange rate had statistically significant (p < 0.05) and negative impact on the agricultural productivity, while implicit price deflator for the agricultural sector had statistically significant (p < 0.001) and positive impact on agricultural productivity in the long-run. The error correction term indicates that the speed of adjustment to the short-run equilibrium was high (79.71%). Hence, reliance on foreign direct investment would have adverse effect on agricultural gross domestic product in the long-run. The Federal Ministry of Agriculture and Rural Development should evolve policies that would guarantee steady inflow of foreign direct investment to agriculture in a manner to reverse the negative impact or explore alternatives. In addition, the Central Bank of Nigeria should adopt a sound monetary policy to attain stability in the exchange rate as well as supply of FOREX to ease purchase of agricultural inputs.